Legal regulation of waste management in Ukraine and the EU - Oleksandr Balobanov (Розвиток методів управління та господарювання на транспорті, 2020)
Ensuring the environment is safe for human life and health is one of the vital goals of the entire world community. Seaports inevitably affect the atmosphere, hydrosphere and soil. The main source of environmental pollution are merchant ships, which produce the most danger for the marine environment. The solution to the problem of waste management should be carried out through the state regulation, which should take into account the national characteristics of the population and the positive experience of European legislation. The author notes that the effective functioning and development of seaports depends on a number of factors, including the level of their technological and technical equipment, development of maritime infrastructure, compliance of the management system with modern international requirements, provision of regulatory framework. The current legislation of Ukraine and the requirements of the European legislation in the field of waste management are considered and analyzed. Approaches to solving the global problem in the context of European integration are proposed, namely: creating the necessary regulatory framework to reduce ship waste and cargo residues into the sea, as well as preventing or limiting the negative impact of seaports on the environment and human health; creation of modern infrastructure. The lack of regulation has a direct impact on the environment, on the efficiency of not only the port and transport industry, but also the economy as a whole. The study aims to highlight a fundamental criterion - waste management in the ports of Ukraine. It is concluded that in Ukraine there is no clear organizational structure of waste management. The author concludes that it is necessary to use European standards for waste management in ports.